Administrasi Manajemen Sekolah dalam Meningkatkan Mutu Sekolah Melalui Pembelajaran Fisika Dengan Mengintegrasikan Seni - Isra, Hutri Handayani; Akmal, Muhammad Syafruddin (Universitas Khairun, 2025)
School management administration plays a strategic role in improving the quality of education. This article discusses how school management administration can improve school quality through Physics learning innovation by integrating elements of art. This interdisciplinary approach is expected to enrich learning methods, improve understanding of scientific concepts, and develop student creativity. The methods used are literature review and conceptual analysis. The results of the study indicate that the integration of art in Physics learning, if managed well through effective school administration, can improve student learning outcomes and improve the image of the school. This article recommends the need for teacher training, provision of facilities, and regular monitoring as steps to strengthen the program. The purpose of this study is to determine school management in improving the quality of education, including: (1) School program planning; (2) Implementation of school programs and (3) Obstacles faced. The purpose of this study is to determine the management of school administration management as an effort to improve the quality of education. The research method is qualitative, this study also uses library research, namely research sourced from library materials. Therefore, what is done is an exploration of a number of data, both primary data and secondary data with the following concrete steps: reading and reviewing in depth primary data such as books, journals, articles, and papers which are the results of dissertation research related to school administration management.